FOREIGN EXPERIENCE AND INNOVATIVE APPROACHES IN TOURISM DEVELOPMENT - Nazarov, Behzod (University Research Base, 2025)
This research paper provides an in-depth exploration of innovative strategies and global best practices in tourism development, with a particular emphasis on the critical roles of urban planning and infrastructure. By examining a diverse range of successful case studies from around the world, the study effectively demonstrates how thoughtful and well-executed city planning, coupled with robust infrastructure, can significantly enhance the overall tourist experience. The analysis of these contemporary approaches and their outcomes aims to offer valuable insights and practical recommendations that can be implemented to improve tourism practices in various designated areas.